Source of phosphine on Venus—An unsolved problem - Bains, William; Seager, Sara; Clements, David L.; Greaves, Jane S.; Rimmer, Paul B.; Petkowski, Janusz J. (Frontiers in Astronomy and Space Sciences, 2024)
The tentative detection of ppb levels of phosphine (PH3) in the clouds of Venus was extremely surprising, as this reduced gas was not expected to be a component of Venus’ oxidized atmosphere. Despite potential confirmation in legacy Pioneer Venus mass spectrometry data, the detection remains controversial. Here we review the potential production of phosphine by gas reactions, surface and sub-surface geochemistry, photochemistry, and other nonequilibrium processes. None of these potential phosphine production pathways is sufficient to explain the presence of phosphine in Venus atmosphere at near the observed abundance. The source of atmospheric PH3 could be unknown geo- or photochemistry, which would imply that the consensus on Venus’ chemistry is significantly incomplete. An even more extreme possibility is that a strictly aerial microbial biosphere produces PH3. The detection of phosphine adds to the complexity of chemical processes in the Venusian environment and motivates better quantitation of the gas phase chemistry of phosphorus species and in situ follow-up sampling missions to Venus.